2018
DOI: 10.2147/ott.s157058
|View full text |Cite
|
Sign up to set email alerts
|

The role of Hippo signal pathway in breast cancer metastasis

Abstract: The Hippo pathway is a novel and highly conserved mammalian signaling pathway. Mutations and altered expression of core Hippo pathway components promote the migration, invasion, malignancy, and chemotherapy resistance of breast cancer cells. In cancer metastasis, tumor cells must detach from the primary tumor, invade surrounding tissue, and enter and survive in a foreign microenvironment. The metastatic potential of breast cancer is closely related to individual patient genetic profile. Nevertheless, the exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 74 publications
(77 reference statements)
1
48
0
1
Order By: Relevance
“…This pathway regulates cellular proliferation and apoptosis and has multiple family members that act as tumor suppressors (73). Activation of the HIPPO signaling pathway has also been shown to antagonize WNT signaling, whereas inhibition of HIPPO signaling (causing YAP hypophosphorylation and nuclear localization) can induce EMT (74,75). Downregulation of HIPPO signaling may therefore be involved in the increase in WNT signaling and EMT seen in the REM-134 RR cell line.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway regulates cellular proliferation and apoptosis and has multiple family members that act as tumor suppressors (73). Activation of the HIPPO signaling pathway has also been shown to antagonize WNT signaling, whereas inhibition of HIPPO signaling (causing YAP hypophosphorylation and nuclear localization) can induce EMT (74,75). Downregulation of HIPPO signaling may therefore be involved in the increase in WNT signaling and EMT seen in the REM-134 RR cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Hippo also controls organ size by inhibiting cell proliferation and promoting apoptosis (31). In turn, as described by Saeg and Anbalagan, the deregulation of Hippo signaling is believed to be responsible for the formation of Cancer Stem Cells (CSCs) in various types of cancer, including BC (32)(33). The proliferation of CSCs is known to be involved with activation of radioresistance.…”
Section: Discussionmentioning
confidence: 98%
“…First, metastasis is an essential hall marker of cancer and always leads to poor survival. [41][42][43] Numerous studies suggested that Tiam1 contributed to invasion and metastasis in various cancers, including osteosarcoma, 44 retinoblastoma, 45 gastric cancer, 46 CRC, [47][48][49][50][51] hepatocellular carcinoma, 25,52 breast cancer, 53 cholangiocarcinoma, 54 cervical cancer, 20 ovarian cancer, 55 nasopharyngeal cancer, 8,16 laryngeal cancer, 56 thyroid carcinoma, 57 nom-small cell lung cancer, 48 pancreatic cancer 6,58,59 and oral squamous cell carcinoma 27 Malliri et al reported that Tiam1 could facilitate E-cadherin-based adhesions between cancer cells in mouse intestinal tumors and human colon tumors, resulting in invasion and metastasis 60 Epithelial-mesenchymal transition (EMT) is a key process of enhancing cancer cell migration, invasion and metastasis. [28][29][30][31] Liu et al reported that Tiam1 overexpression could promote invasiveness and metastasis of thyroid carcinoma in vitro and in vivo by activating Wnt/EMT pathway 57 Similarly, Ding 6 and Yang et al 20 that Tiam1 overexpression could also boost invasion and metastasis of pancreatic cancer and cervical cancer by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%